Challenges and opportunities of curbing urban corruption and building professional integrity: Experiences of planners in South Africa and Zambia. (April 2022) - Alexander, Christian; Berrisford, Stephen; Nkula-Wenz, Laura; Ndhlovu, Dorothy; Siame, Gilbert; Watson, Vanessa; Zinnbauer, Dieter
Abstract: Urban corruption can hinder integrated planning, skew the equitable distribution of public investments, and capture urban management processes to the detriment of the public. Yet, we argue in this article, the city scale has been largely overlooked in contemporary anti-corruption research, and – by the same token – urban scholars only recently started paying attention to the role of corruption in urban development. Based on extensive quantitative and qualitative research with planning professionals in South Africa and Zambia, we firstly explore the complex dynamics of urban corruption and the challenges it poses in the respective national planning spheres. Based on this exploration, we then motivate for the need to move beyond compliance-focused understandings of corruption as the sole basis for developing strategies against city-level corruption. Finally, we outline an agenda for possible future research and action on urban integrity.